Student Mistakes In Solving SPLDV Story Problems: An Analysis Based On Newman's Procedure - Jeklin Nadia Legi; Jorry F. Monoarfa; Vivian E. Regar (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study seeks to characterize the categories of errors students make when solving SPLDV word problems using Newman's method. Descriptive qualitative research methods are employed. This study was conducted in class VIII A at SMP Negeri 4 Touluaan during the even semester of the academic year 2021-2022. The research participants were fifteen students. Then, a test comprised of SPLDV story questions was administered to collect data. The test results were then used to select 5 students at random for interviews, based on their distinct errors. The obtained data was analyzed using the following steps: data reduction, data presentation, and conclusion. Most of the class VIIIA students at SMP N 4 Touluaan made reading errors (4.44%), understanding errors (13.33%), transformation errors (26.66%), process skills errors (48.88%), and mnemonic skills errors (68.88%).